Non-radioisotopic typing of human leukocyte antigen class II genes on microplates - Giorda, R; Lampasona, V; Kocova, M; Trucco, M (INFORMA HEALTHCARE, 1993)
We describe a new nonradioisotopic method for HLA class II molecular typing performed in 96-well plates of the same size as those used in enzyme-linked immunosorbent assays (ELISA) and radioimmunoassays (RIA). Biotinylated sequence-specific oligonucleotide (SSO) probes are bound to avidin-coated plates. Digoxigenin-labeled PCR-amplified DNA samples are hybridized, washed and detected with a peroxidase conjugated antibody assay. The method was tested by performing a partial HLA DQA1 and DQB1 typing on 69 randomly selected blood samples. The results are completely concordant with a traditional SSO-PCR typing performed on the same samples. This procedure is simple, fast and could be adapted for performance in semi-automated or automated fashion using equipment already available for ELISA and RIA assays.